Accident cases of children between 0-6 years brought to the emergency service (Annals of Medical Research, 2021)
Aim: Childhood accidents can lead to consequences threatening the health of child. Especially, the accidents encountered by the child in early childhood are among the causes of death and serious disability. This study aimed to investigate what kind of accidents caused 0-6 age group children to be brought to pediatric emergency services and the frequency of these accidents increase in which age range.Material and Methods: In this study, the files of children, brought to the Pediatric Emergency Service of a Training and Research Hospital due to an accident between the dates of 01.06.2017 and 31.12.2017, were scanned and then examined retrospectively. Obtained data were assessed with SPSS 22.0 program and the frequency and percentage analysis were conducted.Results: 1409 children files that could be accessed in the hospital archive were examined; and it was seen that 0-2 age group children formed the 61.2% part of the cases brought due to accidents, % 57.7 of children were male according to gender data of accident data, while falling and poisoning cases were high in July and August, burn cases were high in December. It was found that the number of children with a diagnosis of falling was higher than other diagnoses.Conclusion: It is identified that adequate measures have not been taken for childhood accidents and the number of children having an accident is quite high for a 6-month period. It is important to inform parents to prevent accidents and to create a safe environment.Keywords: Accident; 0-6 years old children; falling, burn; poisoning.